Intermittent-like synchronization and desynchronization phenomena in a Colpitts network model - Camargo, Victor E.; Louodop, Patrick; Cerdeira, Hilda A. [UNESP]; Ferrelra, Fernando F. (AIP Publishing, 2024)
This study investigates the dynamics of a modified Colpitts oscillator, exhibiting complex periodic and chaotic behaviors. Our research explores the dynamics and synchronization of coupled chaotic Colpitts oscillators, crucial for understanding their potential applications and behaviors. The main discovery is the emergence of a phase in which the systems achieve either complete synchronization or desynchronization. This behavior depends on the values of the coupling parameter. The subsequent challenge involves understanding how the coupling parameter influences the emergence of this synchronization phenomenon.